Understanding the experiences of public experts on COVID-19 in Australia - Dempster, Georgia; Sutherland, Georgina (Frontiers in Communication, 2024)
Public experts emerged as vital media figures during the COVID-19 pandemic, influencing political discourse and health interventions. Our study, based on qualitative interviews with public experts who engaged with Australian media, sought to understand their unique experiences and motivations in a pandemic context. Despite significant negative repercussions such as receiving abuse from the public and dealing with difficult journalists, public experts reported positive experiences, such as having a translatable public health impact, reducing community anxiety, and making research accessible outside of academic environments. This study shows the importance of gaining a deeper understanding of these essential contributors to science communication, particularly in the context of post-normal science during a crisis.